Redução de danos e dependência química na clínica dos CAPS AD: uma convivência possível? - Arnor José Trindade Filho (2018)
The present work proposed to discuss the impasses and interfaces between the apparently antagonistic perspectives of the discursive fields of the Chemical Dependency and the Harm Reduction in the clinic with drug users. To do so, we dealt with questionnaires performed with workers from three Psychosocial Care Centers for users of Alcohol and Other Drugs (CAPS AD) in the metropolitan area of Belo Horizonte, MG: Contagem, Betim and Belo Horizonte. As a methodological reference, we use elements of dialectics and hermeneutics as well as discourse analysis.